Biocompatible and bioreducible micelles fabricated from novel α-amino acid-based poly(disulfide urethane)s: design, synthesis and triggered doxorubicin release1. Issue 33 (7th September 2015) - Lu, Wentao; Wang, Xiuxiu; Cheng, Ru; Deng, Chao; Meng, Fenghua; Zhong, Zhiyuan
<x xml:space="preserve">Abstract</x> Novel α-amino acid-based poly(disulfide urethane)s have been developed for the construction of smart triblock copolymer micelles that show good biocompatibility, fast reductive degradation, and triggered intracellular drug release behavior.